Comparison of the endoscopic thyroidectomy via areola approach and open thyroidectomy: A propensity score matched cohort study of 302 patients in the treatment of papillary thyroid non-microcarcinoma - Li, Yujun; Liu, Zhaodi; Song, Zhuolin; Wang, Yong; Yu, Xing; Wang, Ping (Frontiers in Oncology, 2023)
Background: The endoscopic thyroidectomy via areola approach (ETAA) is widely used in patients with benign thyroid tumors and papillary thyroid microcarcinoma (PTMC). Its safety and complication rates are reported to be similar to the open thyroidectomy (OT). This study aimed to evaluate the safety and feasibility of ETAA, comparing with OT, in the patients with papillary thyroid non-microcarcinoma (PTNMC). Methods: We retrospectively reviewed all patients with PTNMC who underwent ETAA or OT in our hospital from January 2017 to December 2021. A total of 302 patients were matched at a ratio of 1:1 by the propensity score matching (PSM) analysis and surgical outcomes. Safety and feasibility were analyzed between two groups. Results: Before PSM, patients in the ETAA group were younger (p <0.001) and had a larger proportion of female (p <0.001) with lower BMI (p <0.001) comparing with the OT group. It also had a higher proportion of unilateral thyroidectomy (p =0.002). Then propensity score matching was used to create a highly comparable control group. After PSM, the ETAA group had a longer operative time (p <0.001), larger blood loss (p =0.046) and total drainage amount (p =0.035), with higher C-reactive protein (p =0.023) and better cosmetic outcomes (p <0.001). There were no significant differences in the following clinicopathologic characteristics: number of dissected of positive lymph nodes, rate of recurrent laryngeal nerve signal weakened, parathyroid autotransplantation, postoperative pain, hospital stay, complications and oncologic completeness. There was no patient converted to open thyroidectomy in the ETAA group and 2 patients suffered recurrence in the follow-up. Conclusion: ETAA is a safe and feasible surgical approach for patients with PTNMC.